Birth Environments: Emerging Trends and Implications for Design - (:unkn) unknown (My University, 1991)
This monograph describes and critically analyzes the range of birth environments in current use and identifies innovative and successful design features of new maternal care facilities. The monograph offers architects and hospital planners a set of design guidelines for renovating or planning new birth facilities. The recommended design concepts and features are based on users' needs and organizational goals in the context of birth environments. Project funded by the American Hospital Association and by an American Institute of Architects Research Grant.